MENINGKATKAN MOTORIK HALUS ANAK MELALUI KEGIATAN ORIGAMI PADA ANAK KELOMPOK B DI TK TUNAS BANGSA TAHUN AJARAN 2023-2024 KOTA SURABAYA - ana, iva novi; virdaus, varia virdania (MOTORIC, 2024)
This research aims to find out how early childhood fine motor skills are developed through origami paper folding skills at the TUNAS BANGSA Bulak Banteng Kindergarten, Kenjeran District. This research is classroom action research (PTK). The research object taken in this research is the development of fine motor skills in early childhood through origami skills. Data collection was carried out through observation, interviews and classroom action research (PTK) documentation. Carried out in 2 cycles, each cycle held 2 meetings. The procedure in this research has 4 stages, namely planning, implementation, action, observation or observation and reflection. The activity of folding origami paper is an activity that requires more perseverance, precision and concentration. This activity, folding origami paper, is a fine motor development activity which has its own appeal for young children. Because the activity of folding origami paper is like the activity of transforming paper into a beautiful and unique shape. The results of the research show that developing fine motor skills through origami activities in each cycle of children's fine motor skills has increased from pre-cycle 46.6%, in cycle I 73.3%, in cycle II 93.3%, the conclusion of the research is that origami activities can develop fine motor skills in children. Keywords: Fine motor skills, paper folding and early childhood.